There Is No Association Between the Presence of Anti-Thyroid Antibodies and Increased Reproductive Loss in Pregnant Women After Art: A Systematic Review and Meta-Analysis - Schwarze-Meza, J (Sociedade Brasileira de Reproducao Assistida, 2017)
Women submitted to ART treatments represent a select subgroup of individuals. Several studies have described the relationship between TAI and pregnancy outcomes as a result of ART, with contradictory results. The purpose of this systematic review was to determine the association between TAI and the risk of miscarriage in pregnancies resulting from ART. MEDLINE via PubMed, LILACS and Embase were searched for studies published in peer-reviewed journals from 1999 to 2017. The studies were summarized using the fixed effects model and the Peto s method to calculate RR in order to flesh out the association between TAI and spontaneous abortion. Only four papers were included in this systematic review and meta-analysis. Thirty-one miscarriages were observed in 210 clinical pregnancies of women with antithyroid antibodies; and 158 miscarriages were seen in 1,371 pregnancies without antithyroid antibodies. The meta-analysis failed to find an association between TAI and higher risk of reproductive loss, RR=0.94 95% confidence interval: 0.71-1.24; p=0.879. In conclusion, the presence of antithyroid antibodies was not associated with increased reproductive loss in patients submitted to ART treatments. It is our opinion that the presence of antithyroid antibodies should be considered as a secondary biomarker of autoimmune disease, rather than an actual cause of miscarriage in patients undergoing ART. Due to the small amount of evidence on the matter, the determination of TAI before the initiation of ART should be limited to research contexts. © 2017, Sociedade Brasileira de Reproducao Assistida. All rights reserved.